과제2

1153 days 전, connie0526@naver.com 작성

f(x)=sqrt(x^4-6*x+2)/(4*x^2) print diff(f(x), x) 
       
1/4*(2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^2) - 1/2*sqrt(x^4 - 6*x + 2)/x^3
1/4*(2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^2) - 1/2*sqrt(x^4 - 6*x + 2)/x^3
f(x)=sqrt(x^4-6*x+2)/(4*x^2) x0=x;y0=f(x0) df(x)=diff(f(x), x) print df(x) m=df(x0) p1=plot(f(x), (x, -1000, 1000)) show(p1) 
       
1/4*(2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^2) - 1/2*sqrt(x^4 - 6*x + 2)/x^3
1/4*(2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^2) - 1/2*sqrt(x^4 - 6*x + 2)/x^3
#도함수를 구하라. f(x)=1/4*(2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^2) - 1/2*sqrt(x^4 - 6*x + 2)/x^3 x0=x;y0=f(x0) df(x)=diff(f(x), x) print df(x) m=df(x0) p2=plot(f(x), (x, -1000, 1000)) show(p2) 
       
3/2/sqrt(x^4 - 6*x + 2) - 1/4*(2*x^3 - 3)^2/((x^4 - 6*x + 2)^(3/2)*x^2)
- (2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^3) + 3/2*sqrt(x^4 - 6*x + 2)/x^4
3/2/sqrt(x^4 - 6*x + 2) - 1/4*(2*x^3 - 3)^2/((x^4 - 6*x + 2)^(3/2)*x^2) - (2*x^3 - 3)/(sqrt(x^4 - 6*x + 2)*x^3) + 3/2*sqrt(x^4 - 6*x + 2)/x^4